Molecular identification and pathogenic impact of Pythium aphanidermatum on ginger (Zingiber officinale): insights into oxidative stress, antioxidant responses, and mycotoxin profiling - Meena, Mukesh; Yadav, Garima; Sonigra, Priyankaraj; Mehta, Tushar; Nagda, Adhishree; Sahoo, Abhishek; Swapnil, Prashant (Frontiers in Microbiology, 2025)
IntroductionGinger (Zingiber officinale) is an economically significant crop, widely cultivated for its medicinal and culinary applications. However, its production is severely affected by fungal pathogens, particularly Pythium aphanidermatum, which cause substantial yield losses and quality deterioration. This study aimed to identify fungal pathogens associated with ginger rhizome rot through molecular characterization and evaluate their impact on plant physiological and biochemical responses.MethodsFungal isolates were obtained from infected rhizomes and identified through morphological and molecular characterization using ITS1 and ITS4 primers. Pathogenicity was evaluated via in vitro and in vitro assays, with analyses of oxidative stress and enzymatic activity. Antioxidant and phenolic metabolism enzyme activities were measured, and mycotoxin profiling was conducted using column chromatography and gas chromatography–mass spectrometry (GC–MS).ResultsThe results confirmed the presence of P. aphanidermatum, which induced severe oxidative stress in ginger plants, including increased reactive oxygen species (ROS) accumulation, lipid peroxidation, and chlorophyll degradation. Antioxidant enzymes such as ascorbate peroxidase (APX), catalase (CAT), superoxide dismutase (SOD), and glutathione reductase (GR) were significantly upregulated, along with phenylalanine ammonia-lyase (PAL) and polyphenol oxidase (PPO). Mycotoxin profiling revealed secondary metabolites contributing to fungal pathogenicity. Application of fungal crude extracts (F1–F3), 24 h prior to inoculation, significantly reduced oxidative damage and preserved plant physiological integrity, with F1 showing the most effective mitigation.Discussion and conclusionThis study demonstrates that P. aphanidermatum infection imposes severe oxidative stress and physiological damage in ginger, as evidenced by elevated ROS, malondialdehyde (MDA), and disrupted chlorophyll composition. Pre-application of fungal crude extracts alleviated these effects, highlighting their potential role in plant defense. These findings provide new insights into the pathogenic mechanisms of P. aphanidermatum and the phytotoxicity of its metabolites, laying the foundation for future studies on detailed chemical characterization and field validation.